2022
DOI: 10.3390/gels8010063
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate and Chitosan as Components Modifying the Properties of Inulin Hydrogels

Abstract: The aim of the study was to investigate the influence of addition of sodium alginate (SA) and chitosan (CH) on the properties of inulin hydrogels. Inulin hydrogels (20 g/100 g) containing various additions (0.0, 0.1, 0.3, and 0.5 g/100 g) of SA and CH were produced. The hydrogels’ properties were assessed based on the volumetric gel index, microstructure, yield stress, texture, stability, and color parameters. According to the findings, the inclusion of these polysaccharides had no influence on the gelation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…It can be also observed that GG, KG, and PS are more transparent than the other biopolymers (although PS has a higher a* and b* parameter—more yellow tones). The color parameters of inulin hydrogels are in accordance with the available literature [ 19 , 54 ]. Novel edible composite films made of whey protein isolate and zein also showed similar values of the color parameters to those of the pea protein (PP) and wheat protein (WP) samples.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…It can be also observed that GG, KG, and PS are more transparent than the other biopolymers (although PS has a higher a* and b* parameter—more yellow tones). The color parameters of inulin hydrogels are in accordance with the available literature [ 19 , 54 ]. Novel edible composite films made of whey protein isolate and zein also showed similar values of the color parameters to those of the pea protein (PP) and wheat protein (WP) samples.…”
Section: Discussionsupporting
confidence: 61%
“…The high physical stability of PP, GG, KG, INU, and PS might be due to the formation of a network that acted as a stabilizing structure when the samples were subjected to the centrifugal force during the test. Florowska et al, (2022) [ 19 ] in their studies on inulin hydrogels with the addition of sodium alginate and chitosan, also reported the high physical stability of inulin hydrogels. Furthermore, the hydrogel’s water-holding capacity is related to its physical stability [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inulin Branched fructosyl units Typically, inulin properties highly depend on their degree of polymerization [29,30] Pectin Rich in carboxylate units (methyl esters)…”
Section: Polysaccharide Chemical Characteristics Gelling Behavior Ref...mentioning
confidence: 99%